Sistem Pendukung Keputusan Pemilihan Merk Sepeda Motor dengan Metode Simple Additive Weighting (SAW) Pada PT.Glostar Indonesia - Resma Nuraeni; Sudin Saepudin (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Motorcycles are a means of transportation that is widely used by most people because they are more effective and efficient. Many people use motorbikes as transportation to go to and from work. The increase in the number and variety of motorcycle products today has made potential customers have their own choices to choose the right motorbike according to their needs. The purpose of this research is to assist consumers in determining the best motorbike that is right and according to their needs, to determine the choice of this motorbike using the Simple Additive Weighting (SAW) method. The decision of the supporters of this system only compares 3 motorbike products, namely Honda, Yamaha and Suzuki. From the ranking results, it is obtained that V1 is the highest and V3 is the lowest, where V1 is Honda and V3 is Suzuki. The research object was carried out in the Sukabumi Regency by distributing questionnaires and interviewing PT. Glostar Indonesia (GSI) employees.